Genome-wide identification and characterization of the NPF genes provide new insight into low nitrogen tolerance in Setaria - Cheng, Jinjin; Tan, Helin; Shan, Meng; Duan, Mengmeng; Ye, Ling; Yang, Yulu; He, Lu; Shen, Huimin; Yang, Zhirong; Wang, Xingchun (Frontiers in Plant Science, 2022)
Nitrogen (N) is essential for plant growth and yield production and can be taken up from soil in the form of nitrate or peptides. The NITRATE TRANSPORTER 1/PEPTIDE TRANSPORTER family (NPF) genes play important roles in the uptake and transportation of these two forms of N. Here, we identified 92 and 88 putative NPF genes from foxtail millet (Setaria italica L.) and its wild ancestor green foxtail (Setaria viridis L.), respectively. These NPF genes were divided into eight groups according to their sequence characteristics and phylogenetic relationship, with similar intron-exon structure and motifs in the same subfamily. Twenty-six tandem duplication and 13 segmental duplication events promoted the expansion of SiNPF gene family. Interestingly, we found that the tandem duplication of the SiNRT1.1B gene might contribute to low nitrogen tolerance of foxtail millet. The gene expression atlas showed that the SiNPFs were divided into two major clusters, which were mainly expressed in root and the above ground tissues, respectively. Time series transcriptomic analysis further revealed the response of these SiNPF genes to short- and long- time low nitrate stress. To provide natural variation of gene information, we carried out a haplotype analysis of these SiNPFs and identified 2,924 SNPs and 400 InDels based on the re-sequence data of 398 foxtail millet accessions. We also predicted the three-dimensional structure of the 92 SiNPFs and found that the conserved proline 492 residues were not in the substrate binding pocket. The interactions of SiNPF proteins with NO3- were analyzed using molecular docking and the pockets were then identified. We found that the SiNPFs-NO3- binding energy ranged from -3.8 to -2.7 kcal/mol. Taken together, our study provides a comprehensive understanding of the NPF gene family in Setaria and will contribute to function dissection of these genes for crop breeding aimed at improving high nitrogen use efficiency.